KAJIAN ASBABUN NUZUL AYAT TENTANG HUKUMAN POTONG TANGAN: Studi Kritis Tentang Tafsir Surat Al-Maidah: 38 - Amilatul Islamiyah; Khoirul Umami (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2024)
Surah Al-Maidah is the fifth surah in the Qur'an, consisting of 120 verses, and is mostly classified as a Madaniyah surah, though some verses were revealed in Makkah. This surah is known as Al-Maidah because it contains verses discussing the feast requested by the followers of Prophet Isa (verses 112-115). Additionally, it is known by other names such as Al-Uqud (the covenants), Al-Akhyar (the good people), and Al-Munqidzah (the savior). The Asbabun Nuzul (occasions of revelation) of verse 38 of Surah Al-Maidah involves two main stories: the story of a Makhzumiyah woman who stole and the story of Tu’mah bin Ubairiq who stole a coat of armor belonging to Qatadah Ibn Nu’man. This verse was revealed to establish the law of hand amputation for thieves. The contextualization of this punishment in modern times indicates that it has specific criteria, such as the value of the stolen goods and the place from which they were taken. In Indonesia, this punishment has not been implemented despite the majority of the population being Muslim. Discussions about the implementation of hand amputation in Indonesia consider various social and cultural aspects to maintain national unity and cohesion. Asbabun Nuzul dari ayat 38 Surah Al-Maidah melibatkan dua cerita utama: kisah seorang wanita Makhzumiyah yang mencuri dan kisah Tu’mah bin Ubairiq yang mencuri baju perang milik Qatadah Ibn Nu’man. Ayat ini diturunkan untuk menetapkan hukum potong tangan bagi pencuri. Kontekstualisasi hukum potong tangan dalam zaman modern menunjukkan bahwa hukuman ini memiliki kriteria tertentu, seperti kadar barang yang dicuri dan tempat barang tersebut diambil. Di Indonesia, penerapan hukum ini belum dilakukan meskipun mayoritas penduduknya beragama Islam. Diskusi tentang penerapan hukum potong tangan di Indonesia mempertimbangkan berbagai aspek sosial dan budaya untuk menjaga persatuan dan kesatuan bangsa.